Straight impalement. Surgical conduct: About a case - Volonté, M A; Volonté, M A; Otero, J P (Cirugía del Uruguay, 2020)
A new case of rectal penetrating wound, a highly lethal condition, a is reported. The surgical management is discussed: repair of the rectal wound and peritoneal and extraperitoneal drainage. Colostomy was not performed. The post-operative course was satisfactory.